The impact of green technology innovation, pro-environmental behavior and eco-design on green new product success: examine the moderating role of green corporate image - Shahid Mahmood; Asifa Iqbal; El-Sayed M El-kenawy; Marwa M Eid; Amel Ali Alhussan; Doaa Sami Khafaga (Environmental Research Communications)
Environmental consciousness has grown, and businesses have been increasingly compelled to adhere to international treaties and regulations. The present study posits that eco-design, green technology and pro-environmental behavior impact the success of new green products by utilizing green process innovation and green product innovation as mediators, with green corporate image serving as a moderator. Furthermore, this study underscores the important of building a positive green corporate image to enhance the effectiveness of sustainable initiatives in the textile sector. Data for the present study were collected from 756 individuals in top, middle, and low-level management positions in various textile sectors operating in Pakistan, using a standardized questionnaire and appropriate sampling strategy for empirical investigation. Data were analyzed using Smart PLS. The results of this study demonstrate that eco-design, green technology and environmentally conscious behavior positively influence a company’s performance with new products. Green process innovation also mediated the relationship between eco-design, green technology, and pro-environmental behavior and a company’s success with new products. Additionally, the data reveal that a green corporate image moderates the link between green product innovation, green process innovation, and an organization’s performance with new products. The research also indicates that green product innovation does not attenuate the link between a company’s eco-design process and the success of new green products. The current study has significantly implications for management, theory, and practice, as it contributes to the existing literature with empirical research on green technology innovation, pro-environmental behavior, and organizational success in developing new products.